Pretreatment of Sanitary Landfill Leachate with a Natural Polymer Moringa Oleifera (Kacang Kelor) Seeds Extract and Hollow Fibre Microfiltration Membrane - Mohd Ameen, Emad Salim (2001)
Due to population growing affluence, the fast development in industrial sector and improved standard of living, a huge volume of solid waste is being produced. The disposal of this numerous quantity of material in a sanitary landfill conveys with it an inherent potential for pollution of indigenous water resources. A major environmental impact resulting from the disposal of solid waste into a sanitary landfill occurs when water either from rainfall or groundwater passing through the refuse accumulates various contaminants including dissolved organic and inorganic components and decomposition products. This percolated liquid is called 'Leachate'. It is considered very harmful and toxic. Biological treatment is the most common system used to handle the leachate before discharge to water sources. Presence of toxic heavy metal in the leachate limit the activity of microorganisms, resulting in the decrease of the efficiency of the biological treatment to produce high effluent quality that will meet Malaysian Effluent Standard. Therefore a laboratory study using a bench scale model of three unit operations / processes of coagulation using Moringa oleifera seeds as a natural coagulant, flocculation-sedimentation and microfiltration was adopted to treat the leachate from Air Hitam Sanitary Landfill at Puchong, Selangor state of Malaysia. Moringa oleifera had achieved 43.75% Cadmium removal, 21.17% Total Chromium removal, 66.77% Lead removal, and 16% Iron removal. Also 55.42% of Total Suspended Solids, 9.98% of Total Dissolved Solids, and 24.16% of Volatile Suspended Solids were removed from the leachate after coagulation with an effective Moringa oleifera dosage. Micro-filtration hollow fibre membrane used decreased the Turbidity, Colour, Total Suspended Solids, Total Dissolved Solids, Volatile Suspended Solids, and Organic Matter in the leachate by 98.30%,90.30%,99.63%,20.83%,36.63%, and 21.87 respectively. Also it achieved 94% Cadmium removal, 29.81% Total Chromium removal, 73.2% Lead removal, and 18.28% Iron removal. Overall heavy metals removal from the leachate achieved by the bench scale model was 95.83% for Cadmium, 27% for Total Chromium, 79.9% for Lead, and 29.53% for Iron. The results shown that Moringa oleifera is a promising natural polymer for removing heavy metals from the leachate, and may be used as a pre-treatment stage for biological treatment to eliminate a portion of the toxic heavy metals, which limits the activity of micro-organisms in the leachate.